Behaviour of auroras during the Spörer minimum (1450-1550) - W. Schröder (Annales Geophysicae, 1994)
It is shown that such data that exist on auroral activity in the period between 1450 and 1550 do not provide conclusive evidence that some authors have claimed for the existence of the so-called "Spörer minimum" in solar activity during this interval.